Strategi dan Marketing Politik Caleg Anwar Al Sadat Dalam Pileg 2019 Dapil Palembang II Sumsel - Sepriansyah, Muhamad; Yazwardi, Yazwardi; Zalpa, Yulion (Ampera: A Research Journal on Politics and Islamic Civilization, 2021)
The election of legislative candidates is a legitimate link between the people and the government in a democratic society. Political strategy is a political force that will occupy a power in the future, the strategy used is to use battle to win wars and aims to achieve peace. The purpose of this study was to determine the strategy carried out by M. Anwar Al Syadat in the 2019 legislative elections in the Palembang II electoral district. This research is field research or "field research" which is carried out in the real world. The results of field research show that the strategy carried out by M. Anwar Al Syadat in the 2019 legislative election uses a political marketing strategy, namely first, showing a political product which contains the vision and mission and excellent work programs of M. Anwar Al Syadat and the winning team. to be shown to the community in the 9 Districts where the campaign is. Second, this promotion is carried out by means of direct dialogue with the community and through social media such as Facebook and Instagram. Third, determine the price during the campaign, both in the campaign funding process and in building the image price of the legislative candidates. Fourth, the place for the campaign, which at that time was not only focused on 1 sub-district, but all sub-districts in the electoral district of Palembang II.